IMPROVING STUDENT'S WORD UNDERSTANDING THROUGH LISTENING TO SONGS - Dewi Imansyah; Asep Kurniawan (TULIP (Tulisan Ilmiah Pendidikan), 2019)
The objective of this study is to implement the song on improvement students’ vocabulary at MTs Ikhlas Jawilan. In constructing this study, the researcher collected data from the Classroom Action Research. The subjects of this study were 30 students and the researcher used listening test method. The action was done in two cycles and each step has four steps. They were planning, acting, observing and reflecting. Based on the result of cycle I and cycle II that mean score in cycle I is 67 witch percentage of passing KKM is 33,33%. In cycle II mean score is 80,33 with percentage of passing KKM is 83,33%. The use of song in teaching English is effective to improve the students’ vocabulary understanding at class VIII A of MTs Ikhlas Jawilan.